(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, linguocultural science, which is considered one of the leading directions of linguistics, its object, the opinions of scientists, the expression of national characteristic words-realities in the work "Baburnama" in English translations, and the linguocultural significance of it are expressed with the help of examples.